(untitled) (Revista Chilena de Rehabilitación y Actividad Física, 2026)
Abstract. Objective: To evaluate the effects of a neuromuscular training program on social participation, self-perception of health, and functional physical condition in older adults. Methodology: A comparative pre-experimental longitudinal study was conducted in 19 older adults belonging to a senior club in Padre Hurtado commune. Participants were selected through non-probabilistic convenience sampling and included active club members aged 66 to 79 years. Individuals with severe visual impairment, hip or knee prostheses currently undergoing rehabilitation, stroke sequelae, or acute musculoskeletal injuries were excluded. The intervention consisted of 12 training sessions performed twice a week, each one lasting 40 minutes. Results: A pre-post analysis was conducted using non-parametric tests (Shapiro-Wilk and R of Wilcoxon) in older adults undergoing a neuromuscular training program. The results showed significant improvements in functional fitness, self-perceived health (SF-12v2), and self-efficacy for social participation (SOSA). Interpretation using North American norms showed a shift from at-risk ranges to more favorable functional levels. Overall, the findings support the effectiveness of the intervention from a biopsychosocial perspective.